2013
DOI: 10.1002/wrcr.20123
|View full text |Cite
|
Sign up to set email alerts
|

The Millennium Drought in southeast Australia (2001–2009): Natural and human causes and implications for water resources, ecosystems, economy, and society

Abstract: Key Points Drivers and impacts of Australia's record drought were analyzed Impacts accumulated and propagated through the water cycle at different rates Future droughts may not be managed better than past ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
594
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,104 publications
(615 citation statements)
references
References 73 publications
18
594
0
3
Order By: Relevance
“…However, GRACE satellite gravity measurements still proved useful for estimating basin or large regional-scale TWS and GWS changes in Australia (e.g., Leblanc et al 2009;Rieser et al 2010;Awange et al 2011). The MDB experienced a severe drought, termed the Millennium Drought (2001van Dijk et al 2013), during which available in situ groundwater level measurements showed an alarming drop in groundwater storage in the southern MDB .…”
Section: Groundwater Depletion In Southern Murray-darling Basinmentioning
confidence: 99%
“…However, GRACE satellite gravity measurements still proved useful for estimating basin or large regional-scale TWS and GWS changes in Australia (e.g., Leblanc et al 2009;Rieser et al 2010;Awange et al 2011). The MDB experienced a severe drought, termed the Millennium Drought (2001van Dijk et al 2013), during which available in situ groundwater level measurements showed an alarming drop in groundwater storage in the southern MDB .…”
Section: Groundwater Depletion In Southern Murray-darling Basinmentioning
confidence: 99%
“…Model simulations also compared favorably with other methods when evaluated against in situ observations of soil moisture (I. Dharssi, Bureau of Meteorology; personal communication) and evapotranspiration measured at flux towers [Van Dijk and Warren, 2010;King et al, 2012]. Model predictions for Australia have been evaluated against remotely sensed time series of total terrestrial water storage Tregoning et al, 2012;Forootan et al, 2012;Van Dijk et al, 2013], surface soil wetness [Van Dijk and Warren, 2010;Doubkova et al, 2012], vegetation greenness [Van Dijk and Warren, 2010;Van Dijk et al, 2013], and vegetation cover fraction, leaf area, and surface albedo [Van Dijk and Warren, 2010]. The model has also been used in drought analysis and in examining the statistical detectability of land cover impacts on streamflow [Van Dijk et al, 2012b].…”
Section: Prior Evaluation Of the Modelmentioning
confidence: 99%
“…Several studies focused on understanding how the meteorological drought propagates to socio-economic drought (VAN LOON; VAN HUIJGEVOORT; VAN LANEN, 2012;BARKER et al, 2015;WANG et al, 2016;FIORILLO;GUADAGNO, 2010;TIGKAS;VANGELIS;TSAKIRIS, 2012). Quantifying linkages between types of droughts requires continuous monitoring of drought indicators and is critical for drought preparedness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous estimates of the time lag between the onset of meteorological droughts and the impacts on the hydrological system ranged from few months (BARKER et al, 2015;VICENTE-SERRANO;LÓPEZ-MORENO, 2005) to few years (LEBLANC et al, 2009;VAN DIJK et al, 2013;BARKER et al, 2015). Quantifying such time lags is crucial to anticipate the associated impacts and implement mitigation measures to minimize such impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation